2018
DOI: 10.11152/mu-1492
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pancreatic tumors by transabdominal Shear Wave Elastography: preliminary results of a pilot study

Abstract: Transabdominal SWE represents a surrogate but feasible method for differentiation cancer from the normal pancreatic tissue. In a clinical setting, data regarding the stiffness complementary to an ultrasound evaluation could guide high-risk patients for a close-up pancreatic monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…Although the sensitivity was slightly lower, our findings are concordant with results from other authors who reported sensitivity rates of 42% up to 100% for localization and characterization of FPLs using endoscopic US or transabdominal US. 6,11,[12][13][14][15][16][17]27 We found intratumoral indurations of 3 m/s or 28.7 kPa to be reasonable cutoff values during intraoperative application, with a sensitivity rate of 74.4%, though the negative predictive value was only about 41%. These cutoffs can be interpreted as initial reference values for intraoperative pancreas tumor characterization and differential diagnosis using IoSWE, but the identification or confirmation of FPL malignancy was more accurate with IoCEUS.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although the sensitivity was slightly lower, our findings are concordant with results from other authors who reported sensitivity rates of 42% up to 100% for localization and characterization of FPLs using endoscopic US or transabdominal US. 6,11,[12][13][14][15][16][17]27 We found intratumoral indurations of 3 m/s or 28.7 kPa to be reasonable cutoff values during intraoperative application, with a sensitivity rate of 74.4%, though the negative predictive value was only about 41%. These cutoffs can be interpreted as initial reference values for intraoperative pancreas tumor characterization and differential diagnosis using IoSWE, but the identification or confirmation of FPL malignancy was more accurate with IoCEUS.…”
Section: Discussionmentioning
confidence: 64%
“…Thereby, reproducible and quantifiable information about the FPLs' elasticity can be gained, which correlates with the benign or malignant nature of the lesion. 3,[11][12][13][14][15][16] Studies of recent literature proved this advantage of SWE, particularly for small FPLs. 14,17,18 Another important feature that helps distinguish malignant from benign FPLs is their microvascularization.…”
mentioning
confidence: 94%
“…Kawada et al [8] reported the use of strain ratio to distinguish between malignancy and benignancy of pancreatic solid tumours. The evaluation of the pancreatic tumours by transabdominal shear wave elastography was reported by Zaro et al [25] in a pilot studied. The mean SWV Pancreatic Elastography DOI: http://dx.doi.org/10.5772/intechopen.89965 of the pathological parenchyma indicated an increase of the SWV at the tumoral (cephalic) level corresponding to 1.54 ± 0.32 m/s compared to 1.21 ± 0.27 m/s for normal pancreas in the control group.…”
Section: Benign Vs Malignant Mass Pancreatic Lesionsmentioning
confidence: 94%
“…Park et al showed that shear wave elastography can determine the relative stiffness between a lesion and the background pancreatic parenchyma, which is helpful in differentiating benign and malignant solid pancreatic lesions [17]. Zaro et al, also showed that shear wave elastography can indicate an increase of elasticity in the pancreatic tumor, compared to normal pancreas [18]. Although there are multiple challenges to be solved, such as operator dependency or inadequate reproducibility, elastography may contribute to early detection of pancreatic cancer in the future.…”
Section: Pancreatic Anatomy and Tips To Improve Visualization By Usmentioning
confidence: 99%